2020
DOI: 10.1186/s12872-020-01414-3
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled hypertension in Ethiopia: a systematic review and meta-analysis of institution-based observational studies

Abstract: Background: Uncontrolled hypertension is one of the major risk factors of cardiovascular and cerebrovascular diseases. The prevalence of hypertension in Ethiopia is expected to reach up to 30%. The aim of this study was to determine the prevalence of uncontrolled hypertension among hypertensive patients on treatment in Ethiopia. Methods: Electronic databases and search engines including EMBASE (Ovid), PubMed/Medline, and Google Scholar were searched for original records in the English language addressing hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 36 publications
3
30
2
Order By: Relevance
“… 7 10 Unfortunately, the majority of patients’ BP was poorly controlled in most health care settings, especially in countries with minimal resources. 7 , 9 , 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“… 7 10 Unfortunately, the majority of patients’ BP was poorly controlled in most health care settings, especially in countries with minimal resources. 7 , 9 , 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, the result of a systematic review and meta-analysis showed that 48% of patients had controlled blood pressure. 16 However, the magnitude of uncontrolled hypertension showed wide variations ranging from 11% 17 to 70% 18 in individual studies.…”
Section: Introductionmentioning
confidence: 99%
“…Diverging from the results obtained, the metanalysis of Amare et al in Ethiopia found a prevalence of uncontrolled hypertension among hypertensive patients undergoing treatment of 48% [2].…”
Section: Discussionmentioning
confidence: 96%